TO QUESTION ABOUT THE AGE OF THE ISLANDS OF NORTHERN CASPIAN AND THEIR BIOTA - G. M. Abdurakhmanov; A. A. Teimurov; A. G. Abdurakhmanov; Z. I. Soltanmuradova; S. A. Guseinova (Юг России: экология, развитие, 2014)
The article summarizes the different approaches to the explanation of fluctuations in the level of the Caspian Sea and the mechanisms of formation of the islands and the accumulative banks of the Northern Caspian. Also in the article presents data on the taxonomic composition of the biota which indicate the possibility of the existence of islands even in the periods of highest level during the Holocene.